BEEKEEPING OF THE PEOPLES OF DAGESTAN IN THE XIX – EARLY XX CENTURY - Ramazanova, Zoa Buttaevna (History, Archeology and Ethnography of the Caucasus, 2019)
The article is devoted to the study of one of the components of the subsidiary sectors of the economy of the peoples of Dagestan in the XIX – early XX century – beekeeping. Studies of historically developed systems of life support of ethnic groups are particularly relevant at the present time, when traditional economic systems, including ancillary occupations of the peoples of Dagestan, are leveled and disappear. Their study is important not only in the development associated with radical changes in social and domestic life, but also in ethnic and cultural interactions. The relevance of the topic is determined by the recently emerging increased interest in the origins of economic and cultural types. The author made a special emphasis on the study of domestic beekeeping, which was combined with bortnichestvo. When writing the article, General scientific methods were used: (analysis, synthesis, induction), allowing to consider the role and place of beekeeping in the system of auxiliary occupations, to show in it the General and special in connection with various conditions (socio-ecological, ethnographic, ecological) of the development of certain regions of the mountainous Dagestan. However, important for this work was the method of logical research, the task of which is to reveal the role played by the individual elements of the system as a whole. Together with General scientific the article uses private research methods: the identification of a specific, descriptive method, etc. The author gives information from the literature on the development of domestic beekeeping, which at the time was combined with beekeeping, Terekemens, Hvarsins, Genuchtens, Gunzibs, Gogoberins, Surgens, Lezgins. Also based on information from a Review of the Dagestan region is composed of a table on the status of beekeeping in 7 districts of the Dagestan region in 1900: Avar, Gunibsky, Dargin, Kazikumukh, Kaitago-Tabasaran, Kyurinsky and Temir-Khan-Sorenstam. The author concludes that in the XIX – early XX century natural-geographical, socio-economic, ethnic and spiritual factors actively influenced the traditional economic activities, in particular, beekeeping.
Keywords: apiary; honey; a hive; beekeeper; the honey flow; Dagestan; economic-cultural types.